APPARITION D’UN COMMERCE INFORMEL DE PRODUITS PHYTOSANITAIRES DANS LE SUDOUEST DU TOGO - Kokou Etse Madjouma Kanda; Sêmihinva Akpavi; Kpérkouma Wala; Komlan Batawila; Koffi Akpagana (European Scientific Journal, ESJ, 2014)
Methods: The study examines an informal trade of herbicides recently highlighted in localities along border between Togo and Ghana. The methodology is participatory and consisted of surveys, semi-structured individual and focus group interviews conducted with 94 sellers of pesticides and farmers aged 20 to 70 years. Results: 193 commercial products, of which 35% approved, have been identified. They are grouped into 9 active ingredients, in which glyphosate represents 68%. The supply of these herbicides is made from Ghana. 57% of respondents justify the use of herbicides by a lack of manpower, which is proved by national statistics. Conclusion: Sellers’ and farmers’ education level do not allow any adoption of right behaviours to avoid individual risks.